2014
DOI: 10.1016/j.sysconle.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of hybrid stochastic differential equations by feedback control based on discrete-time state observations

Abstract: Recently, Mao (2013) discusses the mean-square exponential stabilization of continuous-time hybrid stochastic differential equations by feedback controls based on discrete-time state observations. Mao (2013) also obtains an upper bound on the duration τ between two consecutive state observations. However, it is due to the general technique used there that the bound on τ is not very sharp. In this paper, we will consider a couple of important classes of hybrid SDEs. Making full use of their special features, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 31 publications
1
88
0
Order By: Relevance
“…Thus the proofs in this work are different from those in [16]. It should also be mentioned that the feedback control based on continuous state observation with a time delay was discussed in [25].…”
Section: D(x(t)) = (F (X(t) R(t) T) + U(x(t) R(t) T))dt + G(x(t)mentioning
confidence: 89%
“…Thus the proofs in this work are different from those in [16]. It should also be mentioned that the feedback control based on continuous state observation with a time delay was discussed in [25].…”
Section: D(x(t)) = (F (X(t) R(t) T) + U(x(t) R(t) T))dt + G(x(t)mentioning
confidence: 89%
“…This strategy is widely known as stabilization by noise [1][2][3][4][5][6][7][8][9]. In general, the stability ensured by this strategy is global asymptotic stability in probability (global ASiP) [10,11], which is the most popular stability notion for the origin of a stochastic system.…”
Section: Introductionmentioning
confidence: 99%
“…Then Mao et al . in provided a better bound on the duration τ between two consecutive state observations and generalized the theory to a class of nonlinear hybrid stochastic systems, and You et al . weakened the global Lipschitz assumption on coefficients and further investigated the asymptotic stabilization of nonlinear hybrid stochastic systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the discrete‐time feedback controls in are based on the discrete‐time observations of the state but they still depend on the continuous‐time observations of the mode. This is perfectly fine if the mode of the system is fully observable at no cost.…”
Section: Introductionmentioning
confidence: 99%